The draft genomes of Elizabethkingia anophelis of equine origin are genetically similar to three isolates from human clinical specimens - Johnson, William L. (PLoS One, 2018)
We report the isolation and characterization of two Elizabethkingia anophelis strains (OSUVM-1 and OSUVM-2) isolated from sources associated with horses in Oklahoma. Both strains appeared susceptible to fluoroquinolones and demonstrated high MICs to all cell wall active antimicrobials including vancomycin, along with aminoglycosides, fusidic acid, chloramphenicol, and tetracycline. Typical of the Elizabethkingia, both draft genomes contained multiple copies of β-lactamase genes as well as genes predicted to function in antimicrobial efflux. Phylogenetic analysis of the draft genomes revealed that OSUVM-1 and OSUVM-2 differ by only 6 SNPs and are in a clade with 3 strains of Elizabethkingia anophelis that were responsible for human infections. These findings therefore raise the possibility that Elizabethkingia might have the potential to move between humans and animals in a manner similar to known zoonotic pathogens.